(untitled) (Revista Brasileira de Iniciação Científica, 2024)
This paper aims at evaluating the impacts and improvements from refurbishments in school buildings, as well as comprising changes in infrastructure and resulting educational benefits. Its central issue refers on how the decision-making processes of school refurbishments influence teaching and learning. Thus, a qualitative and exploratory approach was chosen to answer this question, besides documentary analysis and a case study in a school in Cascavel city in Paraná state. The results have shown that refurbishments that integrate multifunctional areas and educational technologies have potential to significantly improve school performance, by creating more dynamic environments that are adaptable to different teaching methodologies.